(untitled) (E Conference Zone, 2022)
The article analyzes the results of clinical observations on the distribution and etiology, as well as experimental studies on the development of diagnostic and treatment-and-prophylactic measures of rumen acidosis in breeding cows in the conditions of farms of the republic